Is there any effect (S) of fenugreek seeds aqueous extract on the regularity of estrous cycle and quantity of ovarian follicles of female rats? - Allow, Ahmed Kaid Naji; Mohamed Bakrim, Norbaiyah; Yousef, Z.; Al-Ani, Imad Matloub Dally; Hassan, N. M.; Al-Kubaisi, Muna Khaleel Dheyab; Mustafa, M. I (Faculty of Medicine, International Islamic University Malaysia, 2015)

(untitled)
Introduction: The presence of diosgenin in fenugreek seeds is believed to be the active compound responsible for fenugreeks anti-fertility property. Objective: The purpose of this study to evaluate the potential effects of fenugreek seeds aqueous extract (FSA) extract on the regularity of oestrous cycle and quantity of ovarian follicles. Methodology: Thirty two healthy mature female rats were randomly divided into four groups of 8 rats each. The first group A was the control and received distilled water; the B, C and D received 250, 500 and 1000 mg/kg/day FSA extract,respectively, for 15 days. Daily vaginal smear cytology was examined and ovaries of the animals were removed after 15 days for histological study. Results: The results showed a significant (P<0.024) irregularity of oestrous cycle and reduction in relative ovarian weights of experimental animals treated by FSA extract in comparison to the control group. A reduction in the number of secondary follicles and corpora lutea was found in the treated groups as well as an increment in the number of antral follicles in all treated groups when compared with the control. Conclusion: The observation of irregular oestrous cycle, significant decrease in the number of secondary and antral follicles, and significant increase in the number of atretic follicles demonstrated the potential anti-fertility effects of fenugreek seeds on the female rats were found in this study.